Foreign trade regime, exchange rate policy, and the atructure of incentives - Valdés, Alberto; Siamwalla, Ammar (International Food Policy Research Institute, 1988)
This chapter analyzes the combined effect of commercial policy and ex-change rate management on relative prices affecting agriculture. But movements in price of traded products (relative to nontradables) result not only from adjustments in trade policy and the nominal exchange rate but also from the behavior of macroeconomic variables such as wages, capital movements, and fiscal and monetary accounts. Although not treated directly in this chapter, all these variables impinge on the final outcome. We shall omit here discussion of purely domestic policies and constraints that affect incentives to agriculture or major restrictions of movements within the borders of countries resulting from both policy and poor infrastructure.